2019
DOI: 10.3389/fpsyg.2019.01954
|View full text |Cite
|
Sign up to set email alerts
|

The Others Are Too Loud! Children’s Experiences and Thoughts Related to Voice, Noise, and Communication in Nordic Preschools

Abstract: Background High noise levels affect hearing, voice use, and communication. Several studies have reported high noise levels in preschools and impaired voice quality in children. Noise and poor listening conditions impair speech comprehension in children more than in adults and even more for children with hearing or language impairment, attention deficits, or another first language. Aim The aim of this study was to explore how children in Finland, Sweden, and Iceland desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…All noise types taken into account, 37% of the students report having a negative affective reaction to noise, and 55% of them feel the noise in their body. These results corroborate past findings on emotional and physical disturbance of noise in students [ 13 , 17 , 18 , 22 , 23 , 24 , 43 , 45 , 47 ]. Past research has shown body sensations to be a significant part of children’s reactions to noise [ 17 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All noise types taken into account, 37% of the students report having a negative affective reaction to noise, and 55% of them feel the noise in their body. These results corroborate past findings on emotional and physical disturbance of noise in students [ 13 , 17 , 18 , 22 , 23 , 24 , 43 , 45 , 47 ]. Past research has shown body sensations to be a significant part of children’s reactions to noise [ 17 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results corroborate past findings on emotional and physical disturbance of noise in students [ 13 , 17 , 18 , 22 , 23 , 24 , 43 , 45 , 47 ]. Past research has shown body sensations to be a significant part of children’s reactions to noise [ 17 , 22 , 23 , 24 ]. However, to our knowledge, our study is the first study on noise perception to present a comprehensive body map of where students report feeling different types of noises, unsurprisingly with the head, especially the ears and the forehead being reported, but also, the heart, and stomach area, and, for Scraping and screeching sounds, the arms and legs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Past studies have broadly shown a restorative advantage for natural environments as opposed to built environments ( Dzhambov et al, 2021 ), but what is less certain are the specific attributes that make the environment restorative for children. Specifically, we assessed the dimension of sound appeal as contributing to restorative potential as children’s awareness and preference for environment sound strongly differ from those of adults ( McAllister et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children participate in numerous social, athletic, extracurricular, and academic activities, 34 many of which are associated with specific vocal demands. 35 Additionally, children often phonate in suboptimal acoustic environments, such as playgrounds and c rowded or noisy rooms, 36,37 and may not carefully regulate vocal volume or behavior in general. 38 Normative data regarding voice use patterns and symptoms in children are needed to identify risk factors for dysphonia.…”
mentioning
confidence: 99%